It would be really great if I had greater confidence and ability there: Understanding the primary care physician experience with nutrition in training, clinical practice, and interprofessional collaboration - Caitlin A. Hildebrand; Seema Agrawal; Jaclyn Albin; Gary L. Beck Dallaghan; Elizabeth Chen; David Gaviria; Kurt O. Gilliland; Alison Hilton; Thomas C. Keyserling; Elizabeth Mayer-Davis; Alice S. Ammerman (PLoS ONE, 2026)
Background Primary care physicians (PCPs) are on the front lines of health promotion and disease prevention, yet evidence supports a longstanding gap in physicians’ capacity to counsel about diet, a key factor in patient health and chronic disease risk. Momentum to address the nutrition training needs of physicians is growing; however, challenges PCPs experience due to inadequate training are further complicated by clinical practice barriers. This study seeks to better understand the complex problem PCPs face addressing nutrition with patients to inform potential solutions. Methods and findings This qualitative study takes a design thinking approach to understanding the problem by learning from PCPs about their experience, challenges, and priorities addressing nutrition with patients. Findings from semi-structured interviews with 32 PCPs revealed that while they value nutrition and believe they have an important role in addressing diet with patients, their role as a generalist in addressing nutrition lacks clarity. PCPs describe learning their current approach to nutrition primarily outside of formal medical training, resulting in variability and inconsistency in approaches and recommendations and general frustrations about their ability to give actionable guidance. While registered dietitians (RDs) are often viewed as valuable support for patients, PCPs describe multiple challenges to RD utilization and subsequently at times may be the only ones with the opportunity to address diet with patients. Additional system- and societal-level barriers, such as time limitations and the food environment, further complicate PCPs’ experiences advising patients about nutrition. Main limitations of this study are limited generalizability from recruiting graduates of a single medical school and PCPs with greater interest in nutrition or more frustration with their current approach to nutrition may have been more likely to participate. Conclusions Our results support the need to clearly define a realistic role for PCPs as generalists addressing nutrition. Clarified expectations in turn can inform nutrition training of physicians and guiding frameworks and strategies for giving practical, evidence-based nutrition guidance. PCPs also need increased support through access to resources, strategies to improve RD collaboration, and attention to system- and societal-level challenges influencing dietary interventions in primary care.